2021
DOI: 10.1021/acs.nanolett.1c02708
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial Cues Regulated Differentiation of Neural Stem Cells into GABAergic Neurons through Ca2+/c-Jun/TLX3 Signaling Promoted by Hydroxyapatite Nanorods

Abstract: Directed differentiation enables the production of a specific cell type by manipulating signals in development. However, there is a lack of effective means to accelerate the regeneration of neurons of particular subtypes for pathogenesis and clinical therapy. In this study, we find that hydroxyapatite (HAp) nanorods promote neural differentiation of neural stem cells due to their chemical compositions. Lysosome-mediated degradation of HAp nanorods elevates intracellular calcium concentrations and accelerates G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The RNA‐seq results prompted western blot analysis to confirm that the relative protein expression of choline acetyltransferase (ChAT), a AChergic neuron‐specific marker, [ 24 ] GAD65, a GABAergic neuron‐specific marker, [ 25 ] and c‐Fos, a reporter gene for neuronal activation by Ca 2+ influx, [ 5b ] in the NSCs of all groups at 5 days (Figure 5c). The relative protein expression of ChAT, GAD65, and c‐Fos in the Au nanostrip array+ group was the highest than that in other groups.…”
Section: Resultsmentioning
confidence: 99%
“…The RNA‐seq results prompted western blot analysis to confirm that the relative protein expression of choline acetyltransferase (ChAT), a AChergic neuron‐specific marker, [ 24 ] GAD65, a GABAergic neuron‐specific marker, [ 25 ] and c‐Fos, a reporter gene for neuronal activation by Ca 2+ influx, [ 5b ] in the NSCs of all groups at 5 days (Figure 5c). The relative protein expression of ChAT, GAD65, and c‐Fos in the Au nanostrip array+ group was the highest than that in other groups.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether microspheres could function in both cellular support and growth factor release, microspheres were layered with hydroxyapatite crystals via SBF. While hydroxyapatite has traditionally been utilized for osteogenic differentiations, , recent work has demonstrated that hydroxyapatite also promotes neural differentiation and functional neuronal development through enhanced Ca 2+ signaling . HA was deposited onto the entire exposed exterior and interior surfaces of the microsphere, allowing crystal deposition without pore occlusion (Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
“…While hydroxyapatite has traditionally been utilized for osteogenic differentiations, 43 , 44 recent work has demonstrated that hydroxyapatite also promotes neural differentiation and functional neuronal development through enhanced Ca 2+ signaling. 45 HA was deposited onto the entire exposed exterior and interior surfaces of the microsphere, allowing crystal deposition without pore occlusion ( Figure 9 A,B). The first SBF phase deposited on the microsphere surface (HA1) acts as a nucleation site, while deposition of the second phase creates an additional layer (HA2) ( Figure 9 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Neural stem cells (NSCs) have pluripotent and significant regenerative potential, and are proposed for the treatment of neurodegenerative diseases as well as stroke and spinal cord injury. [14][15][16] The fusion of stem cell therapies and nanoparticles (NPs) offers great promise in the study, diagnosis and treatment of neurodegenerative diseases. [17][18][19][20] A growing number of preclinical studies suggest that the transfer of NSCs could lead to potential new treatments for neurodegenerative diseases.…”
Section: Doi: 101002/advs202202475mentioning
confidence: 99%